Correlation of Carcinoma Percentage (CP) in Colorectal Adenocarcinoma with Several Clinical Pathological Aspects in Anatomical Pathology Department Faculty of Medicine Universitas Indonesia/Cipto Mangunkusumo Hospital Jakarta in Year 2012-2013 - Elisabeth Indria Sari; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: Colorectal carcinoma is malignant tumour of the large intestinal epithelial, where more than 90% of colorectal carcinoma is adenocarcinoma. Desmoplastic stroma in primary tumour holds an important role in tumour development process. Mesker et al described carcinoma percentage (CP) evaluation in routine preparations with Haematoxylin-eosin (HE) staining as one of the prognostic factors.Method: This retrospective study was performed by collecting forms and slides of colorectal carcinoma resection cases from the archives of Anatomical Pathology Department FMUI-CMGNH in 2 years period (2012-2013). Collection of clinical data and re-evaluation of HE slides by 2 people which were the writer and supervisor were performed to determine CP value by observing the comparison between tumour percentage and desmoplastic stroma.Results: We included 92 cases of colorectal adenocarcinoma within those 2 years period (2012-2013). Comparison of total cases between male and female was 3:2, age 40 years old were the most commonly found; in regard to location in the colon, most were found in the left side compared to the right side of the colon with the ratio of 3:7. Tumour histological grading with good differentiation were the most commonly found and most pT value being found were pT3; most lymph node involvement was N1. The most CP value attained in every parameter was CP-Low.Conclusion: Carcinoma percentage (CP) which was divided as CP-High and CP-Low could be used as a prognostic factor. In this study, we found more cases of CP-Low compared to CP-High, either based on sex, age, location, degree of differentiation, pT value, or even lymph node involvement. CP-Low which showed worse prognosis could also be used as a marker of patients who were at higher risk of colorectal carcinoma.